Pengaruh Fasilitas Kerja, Gaya Kepemimpinan dan Motivasi Kerja Terhadap Kinerja Karyawan - Nabila Anisah Putri; Herry Sussanto (Journal of Trends Economics and Accounting Research, 2025)
The influence of work facilities, leadership style, and work motivation on employee performance at CV Sebelas Saudara Sejahtera is the objective of this study. By using quantitative primary data, the analysis procedures of this study include normality test, multicollinearity, heteroscedasticity, t-test, F-test, and significance coefficient. In this study, a questionnaire serves as an instrument for collecting data. and the number of valid data successfully collected from respondents is 40. Total sampling, which is a nonprobability sampling method, is used for this study in terms of sampling. SPSS is a statistical data processing software tool used to analyze the data in the study. The research findings show that the variable of work facilities does not have an impact on employee performance, this indicates that even though work facilities are available, it does not directly improve the performance of CV Sebelas Saudara Sejahtera employees. Meanwhile, the variables of leadership style and work motivation have an impact on employee performance at CV Sebelas Saudara Sejahtera. This means that the way leaders lead and the company's ability to motivate employees play an important role in encouraging work improvement. An effective leadership style can create a conducive work environment, while high work motivation encourages employees to be more productive and committed to their duties. For the F test, the significance value is 0.000, which is smaller than 0.05, so work facilities, leadership style, and work motivation simultaneously affect the performance of CV Sebelas Saudara Sejahtera Tangerang employees. The coefficient of determination (R²) value of 0.717 or 71.7% indicates that 71.7% of the variation in changes in employee performance can be explained by variations in work facilities, leadership style, and work motivation. This shows that although work facilities are not individually significant, in the context of a combination of other factors, the presence of work facilities still contributes to improving overall performance.